Seyyid Lokman’s Manzume Concerning the Opening of the Gazanfer Agha Madrasa and the Appointment of Seyfizade Ahmed Efendi as Instructor: A New Manuscript Copy and Text - Günhan Börekçi; Uğur Öztürk (İslam Tetkikleri Dergisi)
This article examines the newly found manuscript copy of a manzume (poetic composition) by Seyyid Lokman written on the occasion of the opening of a madrasa in Istanbul by Kapu Ağası Gazanfer Agha (d. 1603), a prominent political figure in 16th-century Ottoman history. Lokman’s work was first introduced to the scholarly community by Müserret Diriöz in 1978. Since then, this work has been utilized by numerous researchers in reference to Diriöz’s studies which were based on a single copy, but it has neither been subject to any other individual study, nor published in full transcription. Lokman’s composition is rich in content. In his work, there are several details which are not found in other contemporary sources, especially regarding the personality and architectural sponsorship of Gazanfer Agha; his relations with the sultan of the time, Murad III (r. 1574-1595), as well as the statesmen and ulama of that era; the appointment of Seyfîzâde Ahmed Efendi as the first instructor to his madrasa, which was opened immediately following the long Ottoman-Safavid War of 1578-1590; and the first lectures delievered in the new madrasa and the ceremonies and feasts organized upon this appointment. The chief goal of this article is to reevaluate this important historical source based on its second copy and provide a full transcription. Accordingly, we have compared the Süleymaniye Library Ayasofya 4787/1 copy utilized by Diriöz, and the Süleymaniye Kütüphanesi Esad Efendi 3376 copy which we have identified as the second copy. The result of this comparision reveals that the Esad Efendi copy differs in certain respects from the Ayasofya copy, most importantly in that it includes the full text of Lokman’s work. In the remaining parts of our article, we give a summary of this work based on its second copy, and provide the text’s transcription in Latin alphabet as an addendum.